Students Satisfaction with the Laboratory Services and Facilities in the College of Business Laboratory Areas - Violeta Neri; Kristine Rose Necesario; Frances Joy Faniega (Philippine Association of Institutions for Research, Inc., 2023)
Bachelor of Science in Hospitality Management major in Cruise Ship Services is one of the programs offered by John B. Lacson Colleges Foundation-Bacolod. This program provides higher education for students to advance their knowledge and a complete set of facilities for students to use. Several studies addressed the issue of delivering service quality in higher education due to the increasing number of enrollees. As the school undergoes accreditation with the Philippine Association of Colleges and Universities Commission on Accreditation, it seeks to assess if the program meets the stringent requirements continually; hence, it is crucial to carry out this research. The study's main objective was to determine student satisfaction with the services and facilities in the College of Business' laboratory areas. This study was participated by 159 BSHM students. A research-made survey questionnaire was utilized through the use of Google Forms. Frequency count, rank, mean, standard deviation, one-way ANOVA, and Pearson Product Moment Correlation were utilized in the data analyses. The findings showed that the expected service quality attributes, when taken as a whole and when students are grouped according to year level and section, are very much visible. The study revealed a very highly satisfying quality of services in the laboratory area.